Islamic education teacher communication strategies improving the quality of teaching and learning activities at mts hidayatus subban semarang - Fouad Larhzizer; Husna Nashihin; Aliwan; Santi Ratnawati; Siti Qomala Khayati; Triana Hermawati; Mohammad Abdul Munjid (Yayasan Azhar Amanaa Yogyakarta, 2025)
This research aims to analyze the communication strategies of Islamic Religious Education (PAI) teachers in dealing with the characteristics of Generation Z to improve the quality of teaching and learning activities (KBM) at MTs Hidayatus Subban Semarang. Generation Z has a tendency to learn quickly, visually, interactively, and is close to the digital world, so it requires teachers to implement more adaptive and interesting communication. This research uses a descriptive qualitative approach with observation techniques, in-depth interviews and documentation as the basis for data collection. The research results show that Islamic Religious Education teachers employ four main communication strategies. First, they use concise, clear, and relevant verbal language to enhance students' digital experiences, making the material easier to understand. Second, they utilize nonverbal communication such as expressions, eye contact, intonation, and gestures to reinforce moral messages and build rapport. Third, they integrate digital media such as videos, visual graphics, and supporting applications to attract interest and enhance understanding of religious concepts. Fourth, they apply a dialogic approach through discussions, questions and answers, and case analysis to enhance students' active participation and critical thinking skills. These findings conclude that adaptive, varied, and technology-based communication strategies can increase motivation, engagement, and the quality of teaching and learning in Generation Z students. The results of this study are expected to be a reference in developing Islamic Religious Education learning communication models in the digital era.